Unmatched perception of speed when running overground and on a treadmill - Kong, P. W.; Koh, T. M. C.; Tan, W. C. R.; Wang, Y. S. (Gait and Posture, 2012)
This study compared the perception of speed between overground and treadmill running. Twenty-one participants ran overground around an athletic track at their preferred speed for 3 min, immediately followed by a 3-min treadmill run and a further 3-min overground run. During the treadmill run, participants were blinded to the speed display and were free to adjust the speed until it was perceived similar as their previous self-selected overground speed. A video camera was used to determine the average running speed during each overground run. A one-way ANOVA with repeated measures was used to detect differences among the three speeds: overground speed during session 1 (OG1), perceived overground speed on the treadmill (TM), and overground speed during session 2 (OG2). A significant difference among the three running speeds was found (P = .039). Post hoc analyses showed that the treadmill speed was much slower than both overground speeds but the overground speed did not differ between session 1 and session 2 (OG1: 3.99 (0.78) m/s, TM: 2.73 (0.62) m/s, OG2: 3.80 (0.74) m/s). These findings confirmed that one's perception of speed was influenced by the treadmill on which individuals were unable to match their corresponding self-selected overground running speed. The unmatched perception of speed is likely due to the distortion of normal visual inputs resulting from the discrepancy between observed and expected optic flow. Clinicians, therapists and treadmill users should be aware of the different psychological demands between treadmill and overground locomotion when selecting gait speed.